2019
DOI: 10.1007/s13197-019-04048-2
|View full text |Cite
|
Sign up to set email alerts
|

Coumarins content in wine: application of HPLC, fluorescence spectrometry, and chemometric approach

Abstract: In this work, high performance liquid chromatography (HPLC) and fluorescence spectrometry methods for determination of natural coumarins in Tokaj wine were developed and compared. Molecularly imprinted solid phase extraction procedure was applied for sample preparation. The separation of esculin, coumarin, herniarin, 4-methylumbelliferone, scoparone, scopoletin was performed on core-shell C18 type of stationary phase (100 9 4.6 mm, 5 lm) with a gradient elution of mobile phase containing 1% aqueous solution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 32 publications
3
4
0
Order By: Relevance
“…This was consistent with the results of Salagoity-Auguste et al who identified and quantitated 4-methylumbelliferone by fluorescence in French red wines, with values ranging from 0.4 to 0.8 μg/L . More recently, higher concentrations up to 180 μg/L were surprisingly found in wines from the Tokaj region . Nevertheless, in the wines of the present study, 4-methylumbelliferone was present at trace level, far below its detection threshold; therefore, it appeared to have no direct impact on the taste of wine.…”
Section: Resultssupporting
confidence: 93%
“…This was consistent with the results of Salagoity-Auguste et al who identified and quantitated 4-methylumbelliferone by fluorescence in French red wines, with values ranging from 0.4 to 0.8 μg/L . More recently, higher concentrations up to 180 μg/L were surprisingly found in wines from the Tokaj region . Nevertheless, in the wines of the present study, 4-methylumbelliferone was present at trace level, far below its detection threshold; therefore, it appeared to have no direct impact on the taste of wine.…”
Section: Resultssupporting
confidence: 93%
“…Data collected from both analyzes, such as coumarin concentrations in the samples as well as emission spectral data and synchronous fluorescence spectra, were then used to develop the PLS model. Comparing the model developed with the results obtained by HPLC, a good correlation is observed, which supports the above method and model for further use in the analysis of coumarins in wine [93].…”
Section: Spectrophotometric and Spectrofluorimetric Determinationsupporting
confidence: 73%
“…Similarly, Peak 8 presented characteristic bands associated with derivatives of coumaric acid [ 23 ]. On the other hand, for Peaks 12 and 18 , their UV-Vis spectra were characteristic of those reported for coumarin-type compounds [ 25 , 26 , 27 ].…”
Section: Resultssupporting
confidence: 56%